2013
DOI: 10.1186/1472-6831-13-36
|View full text |Cite
|
Sign up to set email alerts
|

Appointment attendance at a remote rural dental training facility in Australia

Abstract: BackgroundNon-attended appointments have impacts on the operations of dental clinics. These impacts vary from lost productivity, loss of income and loss of clinical teaching hours.MethodsAppointment data were analysed to assess the percentage of completed, failed to attend (FTA) and cancelled appointments at an Australian remote rural student dental clinic training facility. The demographic and time characteristics of FTA and cancelled appointments were analysed using simple and multivariate multinomial regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 27 publications
(32 reference statements)
6
34
0
Order By: Relevance
“…32 Some signiicant associations were found in our study between particular appointment booking times and non-attendance indicators, in contrast to other studies that reported no signiicant differences in attendance rates. 36,38,44 Our study's indings showed that appointments booked in the 5:30 to 7:00 pm time frame had the largest proportion of FTA appointments. This higher number could be due to family commitments, transportation dificulties, and/ or tiredness at that time.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…32 Some signiicant associations were found in our study between particular appointment booking times and non-attendance indicators, in contrast to other studies that reported no signiicant differences in attendance rates. 36,38,44 Our study's indings showed that appointments booked in the 5:30 to 7:00 pm time frame had the largest proportion of FTA appointments. This higher number could be due to family commitments, transportation dificulties, and/ or tiredness at that time.…”
Section: Discussionmentioning
confidence: 73%
“…This statistically signiicant difference is consistent with the majority of studies that have also found younger patients to be more likely to not attend appointments. 10,24,36,38,[41][42][43] The strong evidence of non-attendance among younger patients suggests that speciic strategies to improve patient attendance for this group need to be implemented. Improvement may require more than an SMS reminder, such as a telephone call more than 24 hours in advance of the appointment followed up with the SMS reminder 24 hours in advance of the appointment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may reflect worse oral health behaviors and less frequent appointments to the dentist, resulting in an increased risk of dental caries. [21][22][23] In a previous study, it was possible to determine the relationship between socio-economic status and a higher risk of developing oral pathology with painful symptomatology. 24 When analyzing the variable "appointments to the dentist", we found out that the children who reported not having visited a dentist, in the last twelve months, had a higher prevalence of dental caries and reflected a higher value of dmft and DMFT.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the studies listed in the table, other studies analysing patient demographics of Gender and Age (irrespective of a reminder intervention) show an association between these demographic characteristics and general non-attendance (Cashman et al 2004;Perron et al 2010). Other characteristics mentioned in the non-attendance literature include associations with Socio-economic group (Cashman et al 2004;Lalloo & McDonald 2010;McInnes et al 2014) and Asylum seeker status (Perron et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%